Nontraumatic glenohumeral instability and coracoacromial impingement in swimmers - Bak, K. (Scandinavian Journal of Medicine & Science in Sports, 1996)
Competitive swimming is one of the most demanding and time-consuming sports. Swimmers at elite level practice 20-30 h per week. During 1 year's practice, the average top level swimmer performs more than 500,000 stroke revolutions per arm. These innumerable repetitions over many years of hard training together with an increasing muscular imbalance around the shoulder girdle seem to be the main etiological factors in the development of the over-use syndrome swimmer's shoulder. Shoulder pain in swimmers has in general been regarded as synonymous with coracoacromial impingement, i.e. anterior shoulder pain due to rotator cuff tendinitis, but new knowledge suggests that a concomitant glenohumeral instability plays an additional role. The diagnostic complexity of the problem is as challenging as the search for the gold standard of treatment. The condition should ideally be diagnosed as early as possible, and intensive functional rehabilitation of the shoulder girdle including the scapular muscles should be started in order to restore muscle balance. The surgical possibilities include subacromial decompression in cases of purely mechanical impingement. If a painful glenohumeral instability persists after intensive functional rehabilitation, anterior capsulolabral reconstruction can be performed. Still, however, short- and long-term results show that surgery is less successful in elite athletes involved in overhead sports. Prevention protocols include education of coaches in primary injury prophylaxis and the institution of resistance strength training in prepubescent swimmers. Emphasis should be made to improve muscular balance around the glenohumeral and scapulothoracic joints. Scand J Med Sci Sports 1996 Jun;6(3):132-44